Conformationally restricted 3,5-O-(di-tert-butylsilylene)-D-galactofuranosyl thioglycoside donor for 1,2-cis a-D-galactofuranosylation - Tilve, Mariano Javier (2014)
A conformationally restricted 2-O-benzyl-3,5-O-di-tert-butylsilylene-b-D-thiogalactofuranoside donor was prepared from benzyl alpha-D-galactofuranoside and its donor capability was studied for stereoselective 1,2-cis a-D-galactofuranosylation. An unusual chemical behavior on benzylation and hydrogenolysis reactions was observed after the introduction of the 3,5-O-di-tert-butylsilylene protecting group into the galactofuranosyl moiety. The influence of the solvent, temperature and activating system was evaluated. The NIS/AgOTf system, widely used in 1,2-cis b-arabinofuranosylation, was not satisfactory enough for 1,2-cis galactofuranosylation. However, moderate to high alpha-selectivity was obtained with all the acceptors employed when used p-NO2PhSCl/AgOTf as a promoting system, in CH2Cl2 at -78 ºC. The order of the addition of the reactants (premixing or preactivation) did not affect substantially the stereochemical course of the glycosylation reaction. The a-D-Galf-(1-6)-D-Man linkage was achieved with complete diastereoselectivity by preactivation of the conformationally constrained thioglycoside donor.